Interrogating the Impact of Land Use/Land Cover Dynamics in Mbarara City in Southwestern Uganda - Nuwagira, Upton; Yasin, Igga; Nasasira, Perfect (East African Journal of Environment and Natural Resources, 2023)
The urbanization in Mbarara City Southwestern Uganda has increased the number of built-up and small-scale agricultural areas thus escalating pressure on the grassland and woodlot areas hence influencing land fragmentation and slum development. In this study, we focused on land use/land cover dynamics. This helped us to identify land uses that reduce grassland areas, which increases land fragmentation, and slum development. Presumably, the land uses in the area included built-up areas, grassland, small-scale agriculture, and woodlots. Built-up, grassland, and small-scale agriculture were vital for our analysis. We employed remote sensing techniques (Supervised-Maximum Likelihood Classifier) with two cloud-free high-resolution images of 2010 and 2022 in mapping spatial-temporal patterns in built-up, grassland, and small-scale agriculture. Our results evidenced that built-up area increased by (5.14%), grassland declined by (7.1%), small-scale agriculture increased by (2.62%), and woodlots reduced by (0.73%) between 2010 to 2022 and the accuracy assessment for the image classification was (83%). Our study found that an increase in built-up areas and small-scale agriculture led to the decline of the grassland and woodlot areas between 2010 to 2022 with a statistically significant difference (p = 0.03). There was also a strong positive correlation (r = 0.97) between land use/land cover types in 2010 and 2022. Our study recommends that Mbarara City Authority should put strict laws and regulations governing the minimum size of land required during sub-division to avoid land fragmentation which results in increased slum development. Increased land fragmentation may have an intense impact on important ecosystems such as grasslands.
Keywords: Remote Sensing; GIS; Land-Use; Dynamics